On results of freshwater invertebrate studies in Tigireksky Reserve: fauna overview - Kuzmenkin, D. V.; Yanygina, L. V. (Acta Biologica Sibirica, 2018)
The paper presents the integrated results of the faunistic study of aquatic invertebrates from the Tigireksky Reserve as well as their most complete check-list. The hydrobiological studies in the Tigireksky Reserve were carried out in 2000-2009 and covered 15 small and medium-sized rivers, including some small lentic reservoirs. Currently, 206 species of aquatic invertebrates (11 planktonic and 195 benthic) have been identified in streams and water bodies of the Tigireksky Reserve. The bentofauna basis comprises amphibiotic insects of orders Diptera, Trichoptera, Ephemeroptera and Plecoptera.